Money Politics In Local Democracy: A Case Study In The Simultaneous Election Of Village Heads Throughout Bombana Regency In 2022 - Azhari Azhari; La Ode Dedihasriadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
In Bombana district, Southeast Sulawesi Province on February 20, 2022 a democratic party was held through the simultaneous general election of village heads throughout Bombana district which was attended by 109 villages as stipulated in Bombana Regent Decree No. 449 of 2021 Concerning Schedules and Stages of Simultaneous Village Head Elections in 2022. In the implementation of local democracy through simultaneous village head elections, there are many practices of money politics carried out by village head candidates, success teams, and the community itself. The purpose of this research is to find out the factors causing the practice of money politics in the simultaneous village election. The method used in this study is a qualitative method by describing the facts that occur in the field to be explained more deeply through primary data sources, namely interviews, and secondary data, namely books and journals. The results of this study indicate that several factors cause money politics in simultaneous village elections in Bombana district, including the habitual factor that continues to occur at every election moment at all levels of democracy that occurs in Bombana district, and economic factors due to the Covid-19 outbreak that hit Indonesia. nationally 2 years ago, the factor of the absence of a special supervisory agency for village head elections, the factor weak laws and regulations on all hierarchies governing villages, and the absence of political education carried out by the local government and stakeholders in building village community intelligence about the dangers money politic.